2011
DOI: 10.1002/tox.20781
|View full text |Cite
|
Sign up to set email alerts
|

Stage-dependent toxicity of bisphenol a onRhinella arenarum(anura, bufonidae) embryos and larvae

Abstract: The acute and chronic toxicity of bisphenol A (BPA) was evaluated on the common South American toad Rhinella arenarum embryos and larvae by means of continuous and pulse exposure treatments. Embryos were treated continuously from early blastula (S.4) up to complete operculum (S.25), during early larval stages and by means of 24 h pulse exposures of BPA in concentrations ranging between 1.25 and 40 mg L(-1) , in order to evaluate the susceptibility to this compound in different developmental stages. For lethal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 35 publications
(50 reference statements)
0
16
0
Order By: Relevance
“…On the other hand, our test results showed that BPA is moderately toxic in embryos and tadpoles of X. laevis. This lethal effect might be related to the narcotic effects of BPA due to gill circulation, as suggested by Wolkowicz et al (2014). However, no teratogenicity was determined, even in the highest concentrations, in the FETAX assays.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, our test results showed that BPA is moderately toxic in embryos and tadpoles of X. laevis. This lethal effect might be related to the narcotic effects of BPA due to gill circulation, as suggested by Wolkowicz et al (2014). However, no teratogenicity was determined, even in the highest concentrations, in the FETAX assays.…”
Section: Discussionmentioning
confidence: 89%
“…). It is also a good choice to use developmental stages in some specific studies (Aronzon et al ., ; Hutler Wolkowicz et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, the toxicity of xenobiotics to embryos is dependent not only on type, level and duration of exposure but also on developmental stages of exposure (González‐Doncel et al ., ; Burggren and Mueller, ). Stage‐specific susceptibility to chemical exposure has been proven to exist in embryogenesis of several aquatic organisms such as the sea urchin (Cima et al ., ), fish (González‐Doncel et al ., ; Mattsson et al ., ; Shi et al ., ) and frog (Aronzon et al ., ; Svartz et al ., ; Hutler Wolkowicz et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Narcosis is an interesting effect with potential ecotoxicological consequences that might be brought about by numerous structurally unrelated chemicals in relation to their high octanol–water partition coefficients . Bisphenol A and epichlorohydrin, chemicals used to synthesize the BADGE epoxy resin can also cause induced narcosis on R. arenarum larvae .…”
Section: Discussionmentioning
confidence: 99%